Perkembangan Ekspor Karet Alam Indonesia - Hajry Arief Wahyudy; Khairizal; Heriyanto (DINAMIKA PERTANIAN, 2018)
ABSTRACT The purpose of this study was to determine the development of Indonesia's natural rubber exports. The data used are Time Series data from 1996-2016 obtained from various sources such as International Trade Statistics, FAO, United Nation Commodity Trade Statistics and BPS. The research data were analyzed using descriptive analysis. The results showed that the development of Indonesia's natural rubber export volume was increasing, although it fluctuated but still grew positively by 3.34 percent. This increase has an impact on increasing the value of its exports, even the increase is greater than the increase in volume. Over the past 21 years the value of Indonesia's natural rubber exports grew by 9.95 percent. Keywords: Development, Natural Rubber, Exports.